2019
DOI: 10.1021/acsami.9b03731
|View full text |Cite
|
Sign up to set email alerts
|

Ultralight Cellular Foam from Cellulose Nanofiber/Carbon Nanotube Self-Assemblies for Ultrabroad-Band Microwave Absorption

Abstract: Microwave absorption materials (MAMs) with lightweight density and ultrabroad-band microwave absorption performance are urgently needed in advanced MAMs, which are still a big challenge and have been rarely achieved. Here, a new wide bandwidth absorption model was designed, which fuses the electromagnetic resonance loss ability of a periodic porous structure in the lowfrequency range and the dielectric loss ability of dielectric materials in the highfrequency range. Based on this model, a lightweight porous ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…Nanomaterials 2020, 10 6 of 14 carbon crystal plane. With the increase of carbonization temperature, the graphite carbon peak intensity gradually increases from 700 °C to 900 °C, demonstrating that high temperature condition is beneficial to the graphitization of carbon.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nanomaterials 2020, 10 6 of 14 carbon crystal plane. With the increase of carbonization temperature, the graphite carbon peak intensity gradually increases from 700 °C to 900 °C, demonstrating that high temperature condition is beneficial to the graphitization of carbon.…”
Section: Resultsmentioning
confidence: 99%
“…Nanomaterials 2020, 10 10 of 14 Figure 6. Three-dimensional map reflection loss of (a) Co/C@C-700, (b) Co/C@C-800, and (c) Co/C@C- Figure 6e-f show the attenuation constant α and impedance matching ratio of the Co/C@C-700, Co/C@C-800, and Co/C@C-900 composites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, porous structures have been proven to be favorable for prolonging propagation paths and then improving microwave scattering, thus leading to a better microwave absorption performance. For instances, Yin et al presented that the ultra-broad effective microwave band of cellular foam reached 29.7 GHz arising from the well-interconnected porous structure [4]. Li et al reported that porous carbon delivered a minimum reflection loss (RL min ) value of − 56.4 dB, which was owing to the improvement of polarization abilities and multiple reflections [5].…”
Section: Introductionmentioning
confidence: 99%